Circ_0001658 promotes the proliferation and metastasis of osteosarcoma cells via regulating miR‐382‐5p/YB‐1 axis. (22nd November 2019) - Wang, Lisong; Wang, Pengbin; Su, Xiujun; Zhao, Bo
Abstract : Circular RNA (circRNA) can modulate the gene expression via sponging microRNA (miRNA) in multiple malignancies. Nevertheless, the detailed function of circ_0001658 in osteosarcoma (OS) and its regulatory mechanism remain elusive. Real‐time PCR was carried out to detect the expressions of circ_0001658, miR‐382‐5p, and Y box‐binding protein 1 (YB‐1) mRNA in OS tissues. Besides, western blot was done to monitor YB‐1 expression in OS cells. Chi‐squared test was used to analyse the correlation between circ_0001658 and clinicopathologic characteristics of OS patients. CCK8 assay, colony formation assay, flow cytometry, and transwell assay were performed to determine the function of circ_0001658. Moreover, dual‐luciferase reporter gene assay was done to verify the targeting relationship between circ_0001658 and miR‐382‐5p. Compared with adjacent tissues, circ_0001658 displayed a significantly higher expression in OS tissues. Circ_0001658 could facilitate the proliferation, migration, and invasion of OS cells and impede apoptosis by sponging miR‐382‐5p. Further, circ_0001658 was proved to directly and negatively regulate the expression of miR‐382‐5 while positively modulate the expression of YB‐1. Circ_0001658 promotes the proliferation and metastasis of OS cells via modulating miR‐382‐5p/YB‐1 axis. Significance of the study: In recent years, the expression and function of circular RNA in cancer have been the focus of tumour research. The study on circular RNA helps elucidate the molecular pathology of tumorigenesis and cancer progression. This study demonstrated that circ_0001658 promotes the proliferation and metastasis of OS cells via modulating miR‐382‐5p/YB‐1 axis. To our best knowledge, this work is the first to study the expression and function of circ_0001658 in cancer.